2009
DOI: 10.1103/physrevb.80.134517
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of Josephson qubits due to strong coupling to two-level systems

Abstract: We investigate the energy relaxation ͑T 1 ͒ process of a qubit coupled to a bath of dissipative two-level fluctuators ͑TLFs͒. We consider the fluctuators strongly coupled to the qubit both in the limit of spectrally sparse single TLFs as well as in the limit of spectrally dense TLFs. We conclude that the avoided level crossings, usually attributed to very strongly coupled single TLFs, could also be caused by many weakly coupled spectrally dense fluctuators.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…Very similar features have been observed earlier in a related system, namely, a superconducting flux qubit, 10 which suggests that these strongly coupled TLS have the same origin in both flux and phase qubits, even though the degrees of freedom being manipulated are different. Additional evidence against the TLS being an harmonic object ͑as would result from an ensemble of two-level systems forming an effective TLS, 18 for example͒ is provided by experiments trying to pump two excitations resonantly into the TLS, 32 similar to the protocol used in Ref. 16.…”
Section: A Two-photon Spectroscopy Of Four-level Hybrid Quantum Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Very similar features have been observed earlier in a related system, namely, a superconducting flux qubit, 10 which suggests that these strongly coupled TLS have the same origin in both flux and phase qubits, even though the degrees of freedom being manipulated are different. Additional evidence against the TLS being an harmonic object ͑as would result from an ensemble of two-level systems forming an effective TLS, 18 for example͒ is provided by experiments trying to pump two excitations resonantly into the TLS, 32 similar to the protocol used in Ref. 16.…”
Section: A Two-photon Spectroscopy Of Four-level Hybrid Quantum Systemmentioning
confidence: 99%
“…It has been shown that they are coherent and due to their relatively long coherence times can potentially be used to store and retrieve quantum information. 16 In general, two-level systems are considered detrimental to the qubits operation since they introduce additional channels of decoherence 17,18 and therefore, acquiring a more in-depth understanding of their nature is essential. It has been suggested that these TLSs are formed by charged microscopic defects, located inside the insulating tunnel barrier of the Josephson junction ͑JJ͒ ͑Refs.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the time evolution including decoherence, we solve a Bloch-Redfield master equation [16,17] in secular approximation [10] for the density matrix ρ(t) of the coupled system of qubit and memory. We introduce individual relaxation rates for the qubit and memory as γ 1,q/m .…”
Section: Effects Of Decoherencementioning
confidence: 99%
“…Assuming both these quantities to be constant in time, application of an echo pulse after half the evolution time T /2 will cancel the effect of the coherent oscillations. Since we have a coupled system to which we apply this pulse sequence, the resulting effective decay of the qubit state will be strongly influenced by the decay of the memory [10]. In the case where the additional quantum system shows better coherence properties than the qubit, this will allow us to find an effective protection of the qubit state from energy relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Progress towards quantum computing depends on the development of measurement schemes and readout devices. Each readout process requires a finite-time interval during which the system evolves under the effect of the measuring device [5]- [7] and uncontrollable external [8], [9] or intrinsic [10]- [14] noises. This requires improving the quality of the Josephson contacts and effective isolation of qubit systems from the "electromagnetic environment".…”
Section: Introductionmentioning
confidence: 99%